Overview of Water Quality and Challenges - Khan, Ahmad; Rahimi, Soma; Faizi, Hadisa; Sadat, Meena; Laeeq, Sulaiman (Jour Med Resh and Health Sci, 2023)
Water is an essential component of life sustainability, and worldwide, nations have different challenges to access high-quality water that ranges from accessibility, availability, and contamination. Many countries suffer from water-associated diseases and gastrointestinal diseases that have burdened public health and negatively impacted life longevity. In the 21st century, the development and urbanization in different parts of the world have directly or indirectly posed a danger to water quality and resources. Worldwide, governments at national and international levels need to collaborate on multifaceted strategies to ensure water safety. This paper will elaborate on water quality and critical points vital in drinking water management.